Protein contribution to plant salinity response and tolerance acquisition - Kosová, Klára; Práil, Ilja T; Vítámvás, Pavel (International journal of molecular sciences, 2013)
The review is focused on plant proteome response to salinity with respect to physiological aspects of plant salt stress response. The attention is paid to both osmotic and ionic effects of salinity stress on plants with respect to several protein functional groups. Therefore, the role of individual proteins involved in signalling, changes in gene expression, protein biosynthesis and degradation and the resulting changes in protein relative abundance in proteins involved in energy metabolism, redox metabolism, stress- and defence-related proteins, osmolyte metabolism, phytohormone, lipid and secondary metabolism, mechanical stress-related proteins as well as protein posttranslational modifications are discussed. Differences between salt-sensitive (glycophytes) and salt-tolerant (halophytes) plants are analysed with respect to differential salinity tolerance. In conclusion, contribution of proteomic studies to understanding plant salinity tolerance is summarised and discussed.
Keywords: rostlinné proteiny; Stress, Physiological; salinita; Proteomics; Salinity; Salt Tolerance; proteomika; fyziologický stres; Plant Proteins; tolerance k soli; Transcriptome; transkriptom